Радіовиявлення та локалізація радіоакустичних закладних пристроїв - Дудник, О. В. (ХНУРЕ, 2023)
The main stage in radio detection and localization of radio acoustic hidden devices is performed with the help of special hardware and software complexes. They effectively detect signals that carry danger and help in the carrying out special calculations and developing recommendations for improving the security of the premises. The «VOSTOK» hardware and software complex and methods of localizing the hidden devices were considered.
Keywords: радіовиявлення закладних пристроїв